Answer :

Given 2x + 5 ≤ 0 and x – 3 ≤ 0


Let us consider the first inequality.


2x + 5 ≤ 0


2x + 5 – 5 ≤ 0 – 5


2x ≤ –5




(1)


Now, let us consider the second inequality.


x – 3 ≤ 0


x – 3 + 3 ≤ 0 + 3


x ≤ 3


x (–∞, 3] (2)


From (1) and (2), we get




Thus, the solution of the given system of inequations is


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Solve each of theRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics